Exploitation characters of mobile manypositional radio longway measuring system of landing flying apparatuses - Кондрашов, Я. В.; Фиалкина, Т. С. (Problems of Informatization and Control, 2007)
It is carry out the substantiation of necessity putting into exploitation small-dimensions mobile (portable) manypositional radio-longwaymeasuring system of landing flying apparatuses on aerodromes and landing fields of local airlines (LAL), aviation of general allocation (AGA), applying aviation in national economy (AANE)